Perubahan Penggunaan Lahan dan Kesesuaiannya Terhadap RDTR di Wilayah Peri-Urban (Studi Kasus: Kecamatan Mlati) - Eko, Trigus; Rahayu, Sri (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
TheÂ  disproportionÂ  ofÂ  supplyÂ  andÂ  demandÂ  ofÂ  landÂ  oftenÂ  extendsÂ  citiesÂ  toÂ  theirÂ  peri urbanÂ  areasÂ  reducingÂ theirÂ agriculturalÂ  areas.Â  ThisÂ  isÂ  observableÂ  inÂ  Yogyakartaâ€™sÂ  MlatiÂ  sub districtÂ  whichÂ  wasÂ  classifiedÂ  asÂ  aÂ zobidekot (aÂ  regionÂ  dominatedÂ  byÂ  agriculturalÂ  areas)Â  butÂ  lostÂ  301, 9Â  acresÂ  ofÂ  itsÂ  agriculturalÂ  areasÂ  duringÂ theÂ  1996â€2010Â  period.Â  TheÂ  studyÂ  reviewsÂ  bothÂ  theÂ  changeÂ  inÂ  landÂ  useÂ  duringÂ  thatÂ  period;Â  and theÂ mismatchesÂ between theÂ actual developmentsÂ from theÂ DetailedÂ LandÂ UseÂ Plan.Â TheÂ studyÂ analyzesÂ aerialÂ photosÂ  andÂ  satelliteÂ  images throughÂ  overlaysÂ  andÂ  input-outputÂ  analysis,Â  togetherÂ  withÂ  SWOTÂ  analysisÂ  ofÂ  theÂ  landÂ  useÂ  implementation policies.Â  ResultÂ  showsÂ  thatÂ  10,32%Â  ofÂ  Mlatiâ€™sÂ  landÂ  useÂ  changedÂ  duringÂ  theÂ 1996-2010Â  periodÂ  resultingÂ  inÂ  the lossÂ  ofÂ  290,67Â  acresÂ  ofÂ  agricultureÂ  areasÂ  withÂ  asÂ  muchÂ  asÂ  13,12%Â convertedÂ  intoÂ  housingÂ  areas.Â  However,Â  65,%Â  ofÂ  itsÂ  landÂ  useÂ  stillÂ  conformsÂ  toÂ  theÂ  PlanningÂ  Document.Â TheÂ  areaÂ  lacksÂ  legalÂ  aspectÂ  inÂ  itsÂ  landâ€useÂ  planÂ  policyÂ  implementationÂ  sinceÂ  theÂ  PlanningÂ  DocumentÂ  hasÂ notÂ  beenÂ  legalized.Â InstitutionalÂ  aspectÂ  shows consistencyÂ  andÂ  availabilityÂ  ofÂ  adequateÂ  resources,Â butÂ weakÂ  implementationÂ  inÂ  termsÂ  ofÂ  controlÂ  andÂ  law enforcement.Â  Investments,Â  taxÂ  policyÂ  andÂ  illegalÂ changes ofÂ landÂ useÂ threatening theÂ policyâ€™sÂ implementation.